ADVERTISING APPEALS THROUGH INSTAGRAM CAPTION CODE SWITCHING - Irawan, Irma Aulia; Laksman-Huntley, Myrna (International Review of Humanities Studies, 2025)
The COVID-19 disease required everyone to go into lockdown. All activities and communications were carried out through mobile devices, driving online content consumption to double. The Instagram app, which is part of social media, increased its visits by 43 percent during the lockdown of the COVID-19 pandemic. As users turn to social media, influencers are emerging as figures in shaping online interactions and trends. One of the popular French influencers is Léna Mahfouf (@lenamahfouf). As a global fashion influencer, Mahfouf often uses English transitions in her captions. This qualitative research will identify the types of code-switching found with Poplack's theory (1980) and the driving factors, with Hoffman's theory (1991). This research uses the qualitative method with a data collection technique and literature study. The results found that the most common code switching is intra-sentential switching (within sentences) because it is talking about a particular topic, namely fashion. French is identified as a Matrix Language (bilingual first language or dominant language) and English is an Embedded Language (language embedded in the switch). In conducting promotions with code-switching, the most prominent advertising appeals were found, which are the appeal to promote product features (feature appeal) and share the latest information (news appeal) related to fashion.